2015
DOI: 10.1039/c4cp03165b
|View full text |Cite
|
Sign up to set email alerts
|

Long-range influence of steps on water adsorption on clean and D-covered Pt surfaces

Abstract: We have examined water desorption from Pt(111) terraces of varying width and its dependence on precoverage by deuterium (D) with temperature programmed desorption studies. We observe distinct water desorption from (100) steps and (111) terraces, with steps providing adsorption sites with a higher binding energy than terraces. Preadsorption of D at the steps causes annihilation of water stabilization at the steps, while it also causes an initial stabilization of water on the (111) terraces. When the (111) terra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 46 publications
(125 reference statements)
3
36
0
Order By: Relevance
“…Instead of lines, nearly isoenergetic two-dimensional (2D) structures of tetragons, pentagons, hexagons, and heptagons extending across the step onto the terrace are favored. These structures qualitatively explain the absence of a distinct water desorption feature from (111) terrace sites on Pt(533) [24]. Only a high-temperature desorption peak with a lowtemperature shoulder is observed for water coverages up to a monolayer.…”
mentioning
confidence: 50%
“…Instead of lines, nearly isoenergetic two-dimensional (2D) structures of tetragons, pentagons, hexagons, and heptagons extending across the step onto the terrace are favored. These structures qualitatively explain the absence of a distinct water desorption feature from (111) terrace sites on Pt(533) [24]. Only a high-temperature desorption peak with a lowtemperature shoulder is observed for water coverages up to a monolayer.…”
mentioning
confidence: 50%
“…Intuitively, the water chain on the step edge can be viewed as an extended one-dimensional defect when comparing it to the regular hexagonal arrangement of water on the (111) terrace. This explains the absence of a fully developed (111)-like desorption feature observed in TPD experiments for the Pt(533) surface and the appearance of such a peak on the larger Pt(755) and (977) surfaces 22 . This means that the actual influence area of the step edge extends to at least one or two rows of platinum atoms onto the terrace (see figure 5a).…”
Section: D Water Structures At Surface Defects and Implications For mentioning
confidence: 87%
“…For instance, for hydrogen adsorption the Pt(533) surface can be considered to have a "wide" terrace with clear Pt(111)-like features, while for water adsorption the (111) features are absent 22,45 . For instance, for hydrogen adsorption the Pt(533) surface can be considered to have a "wide" terrace with clear Pt(111)-like features, while for water adsorption the (111) features are absent 22,45 .…”
Section: D Water Structures At Surface Defects and Implications For mentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, results from temperature programmed desorption (TPD) experiments on Pt(111) and vicinal surfaces have shown that pre-adsorption of hydrogen, or deuterium, atoms on Pt(111) causes a stabilization of the adsorbed water on the electrode [37][38][39][40][41], together with a small decrease in the H2Oads coverage. Conversely, on {111} vicinal surfaces it weakens the H2O-metal bonding at {110} and {100} steps and, at high coverages, also at {111} terraces [37,[42][43][44]. In contrast, pre-adsorption of hydrogen on Pt(100) destabilizes the adsorbed water [45].…”
Section: Cvs Inmentioning
confidence: 96%